Given
n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n + sin n n = q p
for coprime positive integers p , q , find p + q .
This is a part of the College Calc problem set. You can find more problems here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First note that:
n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n − 1 < n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n + sin n n < n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n + 1
Now consider
L = n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n ± 1 = n → ∞ lim n ( 9 1 0 0 ) n + ( 6 4 3 4 3 ) n ± 1 = n → ∞ lim 9 1 0 0 n 1 + ( 6 4 0 0 3 0 8 7 ) n ± ( 1 0 0 9 ) n = 9 1 0 0
So by squeeze theorem we have n → ∞ lim n ( 3 1 0 ) 2 n + ( 4 7 ) 3 n + sin n n = 9 1 0 0 and p + q = 1 0 0 + 9 = 1 0 9 .
I used the same approach
Here's an overkill approach:
Let's first set all the powers as n only. That is, we want to evaluate n → ∞ lim n ( 9 1 0 0 ) n + ( 6 4 3 4 3 ) n + sin n n .
Let us invoke Theorem 3 of Stolz–Cesàro theorem :
If the sequence ( x n / x n − 1 ) n = 1 ∞ has a limit, then n → ∞ lim n x n = n → ∞ lim x n − 1 x n .
In this case, x n : = ( 1 0 0 / 9 ) n + ( 3 4 3 / 6 4 ) n + ( sin n ) n . Then, n → ∞ lim x n − 1 x n 0 0 0 = = = = ( 1 0 0 / 9 ) n − 1 + ( 3 4 3 / 6 4 ) n − 1 + ( sin n ) n − 1 ( 1 0 0 / 9 ) n + ( 3 4 3 / 6 4 ) n + ( sin n ) n n → ∞ lim ( 1 0 0 / 9 ) n − 1 + ( 3 4 3 / 6 4 ) n − 1 + ( sin n ) n − 1 ( 1 0 0 / 9 ) n + ( 3 4 3 / 6 4 ) n + ( sin n ) n ÷ ( 1 0 0 / 9 ) n ( 1 0 0 / 9 ) n n → ∞ lim ( 1 0 0 / 9 ) − 1 + ( 3 4 3 / 6 4 ) − 1 ⋅ ( 3 4 3 / 6 4 ÷ 1 0 0 / 9 ) n + ( sin n ) − 1 ⋅ ( sin n ÷ 1 0 0 / 9 ) n 1 + ( 3 4 3 / 6 4 ÷ 1 0 0 / 9 ) n + ( sin n ÷ 1 0 0 / 9 ) n 9 / 1 0 0 + 0 + 0 1 + 0 + 0 = 9 1 0 0 . Hence, the limit in question is also equal to 9 1 0 0 . The answer is 1 0 0 + 9 = 1 0 9 .
Problem Loading...
Note Loading...
Set Loading...
Let a n be the expression inside the limit. Note that
( 3 1 0 ) 2 = 9 1 0 0 > 8 = 2 3 > ( 4 7 ) 3 ; ∣ sin n n ∣ ≤ 1 < 2 1 ( 3 1 0 ) 2 n .
Then we may write
2 1 ( 3 1 0 ) 2 n ≤ ( 3 1 0 ) 2 n + ( 4 7 ) 3 n + sin n n ≤ 2 5 ( 3 1 0 ) 2 n 9 1 0 0 ( 2 1 ) 1 / n ≤ a n ≤ 9 1 0 0 ( 2 5 ) 1 / n .
Note that the 1 / n in the exponent approaches zero -- n → ∞ lim ( 2 1 ) 1 / n = n → ∞ lim ( 2 5 ) 1 / n = 1 .
Thus, due to the squeeze theorem , the three expressions all converge to 9 1 0 0 , so that p + q = 1 0 0 + 9 = 1 0 9 .